2008
DOI: 10.1214/07-aap444
|View full text |Cite
|
Sign up to set email alerts
|

Voter models with heterozygosity selection

Abstract: This paper studies variations of the usual voter model that favor types that are locally less common. Such models are dual to certain systems of branching annihilating random walks that are parity preserving. For both the voter models and their dual branching annihilating systems we determine all homogeneous invariant laws, and we study convergence to these laws started from other initial laws.Comment: Published in at http://dx.doi.org/10.1214/07-AAP444 the Annals of Applied Probability (http://www.imstat.or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(71 citation statements)
references
References 27 publications
1
70
0
Order By: Relevance
“…Coexistence in suitable notions should hold except in very few, if not pathological, cases. Some resolutions of Conjecture 3.8 are achieved in [5,7,6,28], since [22, Theorem 1] takes the first few steps to do so. Yet to the knowledge of the authors, the full resolution of Conjecture 3.8 remains open.…”
Section: Invariance Of Equiparity Coexistencementioning
confidence: 99%
See 3 more Smart Citations
“…Coexistence in suitable notions should hold except in very few, if not pathological, cases. Some resolutions of Conjecture 3.8 are achieved in [5,7,6,28], since [22, Theorem 1] takes the first few steps to do so. Yet to the knowledge of the authors, the full resolution of Conjecture 3.8 remains open.…”
Section: Invariance Of Equiparity Coexistencementioning
confidence: 99%
“…The notion of extinction versus unbounded growth is introduced by Sturm and Swart in [28]. We will discuss this notion in more detail later on.…”
Section: Invariance Of Equiparity Coexistencementioning
confidence: 99%
See 2 more Smart Citations
“…With some care, it can be shown that this implies that the process spends a zero fraction of time in states y with |y| = N + 2, completing the induction step. This argument is written down more carefully in [SS08a]. Formula (3.65) of that paper has to be slightly modified in our situation since we only know that the boundaries of type 01 are unstable.…”
Section: Proof Of Lemma 26mentioning
confidence: 99%